Panmorphic Crisis: Cultural Rupture and Systemic Change - Simon, Gail (Murmurations: Journal of Transformative Systemic Practice, 2021)
The systemic community has cultivated a talent for living with perturbation and a graceful approach to not knowing. In this extremely unsettled era of what I am calling panmorphic crisis so much is in urgent need of our attention. In this paper, I discuss some of the many systems in play creating this panmorphic crisis and discuss the impact of changing temporality. Our existing approaches to therapy and the training of practitioners may not be enough to see us out of one era and meet the needs of a new, emergent world. To create a state of preparedness to change may involve some degree of fundamental overhaul structurally and theoretically. I go on to consider approaches to disruption and consider the homeostatic pull towards restorative positions. Crises create opportunities for not only exploring ideas and practices which we take for granted but also for re-organising the cultural foundations on which we build worlds with each other. I reflect on how the myth of return-to-normal is a dangerous agenda when the culture being restored is infused with historical social injustices. In order for systemic therapy and training programmes to make changes that are culturally relevant, we need to study and alter the impact on our work of colonising and pathologising practices and theory. I discuss systemic liminality, its limits and the impact of disruption to our cultural rhythms. Later, I propose the concept of Stolpersteine, stumbling blocks, to help us encounter hidden histories and our prejudices, and offer some questions for us to consider in our undertaking to decolonise and depathologise our practice and theory to meet the challenges of transmaterial living systems.